Increasing Managerial Effectiveness And Organization Commitment Through Strengthening Personality And Managerial Roles - Muhammad Sulhan; Didik Notosudjono; Widodo Sunaryo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The manager's main goals for his employees are to maximize job performance and ensure them remain working at the company for a significant period of time. This research aims to prove the influences of school principals’ personality and managerial roles on their managerial effectiveness and organizational commitment. This is non-parametric research as the totally population of 136 private elementary school principals at South Jakarta Indonesia are all taken as the sample. The data was collected by using questionnaire forms and analyzed by applying PLS-SEM (Partial Least Square – Structural Equation Modelling). The results show that school principals’ personality and managerial roles have direct and indirect positive influences towards their managerial effectiveness and organizational commitment. Discussion of the research findings and their implications as well as suggestions are further explored at the end of the article.